2017
DOI: 10.1016/j.clinph.2017.07.414
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit remodelling in multifocal motor neuropathy: The importance of axonal loss

Abstract: Motor unit remodelling in multifocal motor neuropathy: the importance of axonal loss, Clinical Neurophysiology (2017), doi: http://dx.doi.org/10. 1016/j.clinph.2017.07.414 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
4
20
1
2
Order By: Relevance
“…Although the previously mentioned scan parameters give information about axonal excitability, denervation, and reinnervation, returners, in our opinion, may enhance the CMAP scan analysis. In some scans, Although there is one study providing a lesser lower limit for MScanFit MUNE, 41 our cutoff values were similar to those described in other reports. 42,43 In addition to being sensitive for discriminating ALS, MScanFit MUNE and CMAP scan parameters were highly correlated with one another.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the previously mentioned scan parameters give information about axonal excitability, denervation, and reinnervation, returners, in our opinion, may enhance the CMAP scan analysis. In some scans, Although there is one study providing a lesser lower limit for MScanFit MUNE, 41 our cutoff values were similar to those described in other reports. 42,43 In addition to being sensitive for discriminating ALS, MScanFit MUNE and CMAP scan parameters were highly correlated with one another.…”
Section: Discussionsupporting
confidence: 87%
“…Although there is one study providing a lesser lower limit for MScanFit MUNE, our cutoff values were similar to those described in other reports . In addition to being sensitive for discriminating ALS, MScanFit MUNE and CMAP scan parameters were highly correlated with one another.…”
Section: Discussionsupporting
confidence: 85%
“…Mathematical modelling suggested that these changes were best modelled by reduction in both Na + and K + channel function. Marked reduction in motor unit numbers associated with strikingly enlarged motor units have been identified distal to the site of block in patients with MMN . Furthermore, axonal degeneration has been shown to be strongly associated with block suggesting that the same pathophysiology is likely to account for both processes .…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, MScan has been shown to be a fast, sensitive and reproducible method, which may be helpful in diagnoses and monitoring disease progression in neuromuscular disorders, particularly amyotrophic lateral sclerosis (ALS) (Jacobsen et al , 2017). So far the only published study of MScan in neuropathy has been one on multifocal motor neuropathy, which showed decreased MUNE values and increased motor unit sizes, whereas CMAP amplitudes were well-preserved (Garg et al , 2017). MScan has not previously been tested in diabetic neuropathy.…”
Section: Introductionmentioning
confidence: 99%